The female Odyssey in two Balkan novels: Gabriela Adameșteanu’s The Meeting and Dubravka Ugrešić’s The Ministry of pain (Colloquia Comparativa Litterarum, 2025)
This article examines two Balkan novels in which memories, as fragments woven into the textual fabric of the autobiographical, define the museum-like narrative structure. The focus of the comparative analysis is on the female voice, which dynamises the museum as a “place of memory” in the novel through the war theme. By replacing the lost home with a kind of a mobile ‘museum-novel’ (as a specific type of novel, the genre of exile), writers such as Gabriela Adameșteanu (Romania) and Dubravka Ugrešić (Croatia) problematize the image of the waiting woman Penelope, transforming their novels into a female Odyssey between personal and public, authentic and imaginary, past and present, continuity and discontinuity, myth and history.
Keywords: female voice; female Odyssey; war; memory; mobile ‘museum-like’ novel; Gabriela Adameșteanu; Dubravka Ugrešić